The role of formulation on the pharmacokinetics of antiretroviral drugs - Diane Et Bastiaans (2018)
Introduction: A multitude of antiretroviral drug formulations are now available for HIV-infected adults and children. These formulations include individual and co-formulated drugs, many of which are also supplied in generic versions. Many antiretroviral drugs have a low aqueous solubility and poor bioavailability. Drug formulation can significantly affect bioavailability, and given the increasing number of new formulations and drug combinations, it is important to be aware that formulation can influence the pharmacokinetics of antiretroviral drugs.Areas covered: This review provides an overview of studies assessing the pharmacokinetics of different antiretroviral drug formulations in adults and children, including fixed-dose combinations. For some antiretroviral drugs, differences in pharmacokinetics have been described, with largest differences in exposure when a liquid formulation is compared to a tablet or capsule formulation. Biopharmaceutical properties of antiretroviral drugs relevant to bioavailability are discussed.Expert opinion: Antiretroviral drug formulations and their excipients can significantly impact drug exposure. However, this is not yet fully recognized. It is important to realize that children use different formulations than adults. Effort should be made to ensure that adequate drug exposures are achieved to treat HIV-infected children. In addition, manipulation of drug formulations may lead to differences in pharmacokinetics.© 2014 Informa UK, Ltd.